Given f(x) = 4x + 13 and g(x) = 10x − 2, solve for (f + g)(x) and select the correct answer below.
(f + g)(x) = 14x + 15
(f + g)(x) = 14x + 11
(f + g)(x) = 6x + 11
(f + g)(x) = 6x + 15

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

@Vocaloid

add both function f(x)+g(x)

how would i do that just add f(x) + f(x)

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.